Dating violence (DV): a systematic meta-analysis review - Gracia-Leiva, Marcela; Puente-Martínez, Alicia; Ubillos-Landa, Silvia; Páez-Rovira, Darío (Anales de Psicología / Annals of Psychology, 2019)
This study summarizes the results of meta-analyses about risk and protective factors related to dating violence (DV). Fifteen studies were included from 1997 to 2018, N = 1784018. The results were classified according to ecological theory. The Zr’s were calculated for each factor and level of analyses, including the differences between victimization and perpetration effect sizes. According to the level of analysis, results showed that the effect sizes were greater for: (1) individual level: cigarette smoking, adolescent pregnancy (victimization) and sex (perpetration/victimization); (2) microsystem: peer sexual harassment, (victimization), peer DV, deviant peers and family violence (perpetration/ victimization); (3) Exosystem: age (victimization) and violent neighborhoods (perpetration/ victimization), and (4) macrosystem: cultural minority and disadvantaged neighborhoods (perpetration / victimization). DV protective factors which had lowest effect sizes were: parental and peers support; and highest effect sizes were in the exo and macro-level, and then in individual and micro-level. Furthermore, statistically significant differences between total effect sizes were found, being higher to victimization than perpetration. Delimiting the most important risk and protective factors on DV have important implications for prevention and intervention.